Health and the Built Environment: Exploring Foundations for a New Interdisciplinary Profession. (21st August 2012) - Kent, Jennifer; Thompson, Susan
Abstract : The supportive role of the built environment for human health is a growing area of interdisciplinary research, evidence-based policy development, and related practice. Nevertheless, despite closely linked origins, the contemporary professions of public health and urban planning largely operate within the neoliberal framework of academic, political, and policy silos. A reinvigorated relationship between the two is fundamental to building and sustaining an effective "healthy built environment profession." A recent comprehensive review of the burgeoning literature on healthy built environments identified an emergent theme which we have termed "Professional Development." This literature relates to the development of relationships between health and built environment professionals. It covers case studies illustrating good practice models for policy change, as well as ways professionals can work to translate research into policy. Intertwined with this empirical research is a dialogue on theoretical tensions emerging as health and built environment practitioners and researchers seek to establish mutual understanding and respect. The nature of evidence required to justify policy change, for example, has surfaced as an area of asynchrony between accepted disciplinary protocols. Our paper discusses this important body of research with a view to initiating and supporting the ongoing development of an interdisciplinary profession of healthy planning.